Vulnerability and Social Resilience of Communities to Floods in Aceh - Yulia Hairin Nur; Putri Prastika; Miftahul Jannah (International Journal of Science and Environment (IJSE), 2026)
This study aims to determine the vulnerability and social resilience of the Krueng Geukueh Village community, Dewantara District, North Aceh Regency, in facing flood disasters. The study used a descriptive qualitative approach with data collection techniques such as in-depth interviews, participatory observation, and document study. The results showed that the community faced high social vulnerability due to the location of houses in lowlands near rivers, the income of residents who are mostly traders with limited incomes, and limited access to information related to flood warnings. The severity of the flood in November 2025 was exacerbated by river overflows from Sawang District, which submerged residents' homes and public facilities such as PIM Hospital up to the roof. Nevertheless, the community demonstrated strong social resilience through mutual cooperation, social networks, adaptation strategies such as small boats and river monitoring, and coordination with village officials. Solidarity and cooperation among residents helped mitigate the impact of flooding, protect residents, and accelerate recovery. This study confirms that social vulnerability and social resilience are interconnected, where resilience emerges as a community response to the flood risks they face. These findings can serve as a reference for village governments and related parties to improve early warning systems, emergency response training, infrastructure improvements, and economic support for residents to strengthen community resilience to flooding.